A case study of international instructors' experiences of English-medium instruction policy in a Korean university. Issue 4 (2nd October 2018) - Kim, Jeongyeon; Tatar, Bradley
ABSTRACT: In the midst of increasing global economic competition, higher education (HE) institutions in many non-English-speaking societies have expanded the extent of internationalization through the recruitment of international faculty members to their campuses and the adoption of educational policies such as English-medium instruction (EMI). Despite growing diversity in HE, little is known concerning the international faculty members' perceptions and practices in relation to EMI policies. This case study examined international instructors' experiences of teaching subject courses in English in a Korean university. A mixed method approach was taken with respect to the challenges of EMI with a questionnaire administered to 18 international instructors and in-depth qualitative interviews carried out with 5 of these instructors. The analyses revealed that the participants were dissatisfied with the lack of interaction between Korean and international students. Notably, without sufficient knowledge of the local language, the participants explicitly affirmed the effects of the local, Korean language on improving interaction and participation. They also provided tasks which local and international students should perform collaboratively in a team. The findings are discussed in terms of how EMI should be implemented to overcome locally bound constraints in a non-English-speaking context and to embrace the emerging needs of international stakeholders.